Characterization of Organic Acid Producing Aspergillus tubingensis FMS1 and its Role in Metals Leaching from Soil. Issue 4 (20th April 2020) - Din, Ghufranud; Hassan, Abrar; Rafiq, Muhammad; Hasan, Fariha; Badshah, Malik; Khan, Samiullah; Chen, Gao; Ripp, Steven; Shah, Aamer Ali
Abstract: Metallotolerant fungi are known for their ability to adapt to high concentrations of heavy metals by producing extracellular metabolites. We isolated an acid-producing filamentous fungus, designated as strain FMS1, from metal-polluted soil and identified as Aspergillus tubingensis by sequence analysis of internal transcribed spacer regions. Physicochemical conditions for growth as well as maximum tolerance to various metals was determined. The carbon source was optimized for maximum yield of various organic acids that were finally characterized as well as quantified through high-performance liquid chromatography (HPLC) analysis. Moreover, these organic acids were applied for leaching of heavy metals from metal contaminated soil. Three organic acids were produced in high concentration, gluconic acid (265 mM), oxalic acid (24 mM), and fumaric acid (0.34 mM) in the presence of sucrose, hence considered it as an ideal carbon source. The highest leaching efficiency with organic acids from strain FMS1 was observed for cadmium (58%), cobalt (53%), and nickel (52%) after 28 days soil incubation. Additionally, these organic acids were found to leach out heavy metals from soil as well. It is concluded that the above-mentioned results could be of great interest for bioleaching and may be applied for efficient and cost-effective bioremediation of metal-polluted soil.